Kajian Sosiologi Sastra dalam Puisi Sajak Orang Kepanasan Karya W.S Rendra - Yusuf Selamet (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Literary works always contain the author's perspective on reality as a social institution created by the author. These problems are often combined into a view or criticism of life. This certainly describes social life as a reality that occurs in an environment. One type of literary work that contains a view of reality is W.S Rendra's poem entitled